Hydrobiological studies on the Vaal River and some of its tributaries, including an introduction to the ecology of Simulium in its lower reaches - Chutter, F M (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 1967)
The studies on the Vaal River and its tributaries presented here, were carried out for a variety of reasons. Prominent among them were several of immediate practical importance, such as the need to know the pollution status of waters which ultimately form the major supply for the Witwatersrand urban and industrial complex, and the need for background data on a stretch of the river which was to be insecticided to control a Simulium pest. However the results of such work can often be used for wider purposes. In this thesis they are used to examine the major factors thought to govern the distribution and abundance of the invertebrate Metazoa in the river. Introduction, p. 2-3.
Keywords: Freshwater biology; Freshwater animals; Freshwater ecology